A rechargeable lithium-O2 battery with dual mediators stabilising the carbon cathode - Gao, X; Chen, Y; Johnson, L; Jovanov, Z; Bruce, P (Nature Publishing Group, 2017)
At the cathode of a Li-O2 battery, O2 is reduced to Li2O2 on discharge, the process being reversed on charge. Li2O2 is an insulating and insoluble solid, leading ultimately to low rates, low capacities and early cell death if formed on the electrode surface, problems overcome by forming/decomposing Li2O2 from solution. A Li-O2 cell is described that decouples completely the electrochemistry at the cathode surface from Li2O2 formation/decomposition. Mediators on discharge (2,5-Di-tert-butyl-1,4-benzoquinone [DBBQ]) and charge (2,2,6,6-tetramethyl-1-piperidinyloxy [TEMPO]) transfer electrons between the cathode surface and Li2O2. The cell cycles with a capacity of 2 mAh cm-2areal at 1 mA cm-2areal with low polarisation on charge/discharge, indicating that dual mediators combined with a true gas diffusion electrode could deliver 40 mAh cm-2areal at rates >> 1 mA cm-2areal. Arguably, the most important advantage of dual mediators is they avoid instability at the carbon cathode. Carbon is the most attractive material for the porous cathode in Li-O2 cells, but is too reactive degrading to Li2CO3. By forming/decomposing Li2O2 in solution and not in intimate contact with the carbon, by avoiding high charge potentials and because only mediators transfer electrons at the carbon surface, carbon instability is avoided (< 0.008 % carbon decomposition per cycle compared with 0.12 % without mediators), addressing one of the biggest barriers to the progress of Li-O2 cells./p>